دراسة أثر سياسة الانفاق الحكومي و السياسة النقدية على مستوى التضخم في الجزائر بتطبيق النماذج الديناميكية(ALMON ,KOYCK ) خلال 1995-2021: Studying the effect of government spending policy and monetary policy on the level of inflation in Algeria by applying dynamic models (ALMON, KOYCK) during the period 1995-2021 - مسعودي مليكة; ترقو محمد; بلعزوز بن علي (Journal of North African Economies, 2025)
This study aims to build a dynamic model that helps in making decisions related to curbing inflation in Algeria based on the data available in the World Bank's publications during the period (1995-2021). To show the effect of economic variables on each other over time, and to obtain results close to economic reality, we used time-lagging variables to estimate the inflation equation using the two dynamic models "ALMON" and "KOYCK". According to the results of the estimation obtained from the Eviews 09 statistical program, the parameters estimated according to the "KOYCK" model are better than the parameters estimated according to the "ALMON" model by obtaining estimates consistent with economic theory and with the actual reality supported by statistical theory.